Capital Budgeting Analysis of Door-to-Port Container Train Transport from Gedebage Container Terminal to JICT Port Project - Hartasantoso, Fakhrul; Faturohman, Taufik (JURNAL SOCIAL LIBRARY, 2024)
This research aims to analyze the feasibility of the project for KAI. In this research, researchers used capital budgeting analysis and risk analysis. For the capital budgeting analysis, there are several parameters to be considered, namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period and Profitability Index based on the calculation of free cash flow to the project. For the risk analysis, the author used sensitivity analysis and monte carlo simulation. In this research, researchers develops three scenarios based on different components such as: (1) percentage of Non-Contract IMO BMN, (2) Track Access Charge and (3) Price of Train Transport. Out of the three scenarios, the third scenario was the best scenario with the percentage of Non-Contract IMO BMN was 0%, track access charge was IDR 1/GT-Km and Price of Train Transport was IDR 4,700,000. Based on the calculation of discounted cash flow, the NPV was IDR 690 million, the IRR was 55%, Payback Period in 2.94 years and Profitability Index was 2.29. Based on the parameters, the project was defined feasible only if the condition in the third scenario met. There are several variables that influence the feasibility for the project, namely Price of Train Transport, percentage of Non-Contract IMO BMN, market growth and inflation rate.